Ultraviolet radiation accelerates NRas‐mutant melanomagenesis: A cooperative effect blocked by sunscreen. (4th July 2017) - Hennessey, Rebecca C.; Holderbaum, Andrea M.; Bonilla, Anamaria; Delaney, Conor; Gillahan, James E.; Tober, Kathleen L.; Oberyszyn, Tatiana M.; Zippin, Jonathan H.; Burd, Christin E.
Summary: To mitigate melanoma risk, sunscreen use is widely advocated; yet, the ability of sunscreens to prevent melanoma remains controversial. Here, we test the tenet that sunscreens limit melanoma risk by blocking ultraviolet radiation (UV)‐induced DNA damage using murine models that recapitulate the genetics and spontaneous evolution of human melanoma. We find that a single, non‐erythematous dose of UV dramatically accelerates melanoma onset and increases tumor multiplicity in mice carrying an endogenous, melanocyte‐specific NRas 61R allele. By contrast, transient UV exposure does not alter tumor onset in mice lacking p16 INK 4a or harboring an NRas 12D allele. To block the rapid onset of melanoma cooperatively caused by UV and NRas 61R, we employed a variety of aerosol sunscreens. While all sunscreens delayed melanoma formation and blocked UV‐induced DNA damage, differences in aerosol output (i.e., amount applied/cm 2 ) caused variability in the cancer preventative efficacy of products with identical sunburn protection factor (SPF) ratings.